Evidence From Dissolved O2 Isotopes in North Atlantic Deep Water for a Recent Climatic Shift. Issue 3 (1st February 2023) - Musan, Israela; Gildor, Hezi; Barkan, Eugeni; Smethie, William M.; Luz, Boaz
Abstract: Anthropogenic‐induced variations of the Atlantic Meridional Overturning Circulation (AMOC) and the associated Deep‐Water Formation (DWF) are a major concern. Using measurements of triple oxygen isotopes in the deep North Atlantic, we present novel evidence for a dramatic decadal to centennial shift in ocean conditions at the source region of DWF. These measurements suggest a recent decrease in the percentage of photosynthetic O2 derived from the source regions of AMOC in the Nordic Seas compared to the Little Ice Age. 1‐D model simulations suggest that a reduction in photosynthetic O2 production can explain the observed decrease. Alternatively, it may indicate a substantial decrease in sea‐ice cover and thus increased air‐sea gas exchange, bringing the isotopic composition of O2 closer to equilibrium with the atmosphere. Our novel data can serve as a benchmark for climate models. Plain Language Summary: In this study, we use the isotopic signature of dissolved oxygen gas in the deep North Atlantic Ocean to demonstrate a recent dramatic change in the Nordic Seas. Water in the deep Atlantic at present was at the surface of the Nordic Seas several hundred years ago, during the Little Ice Age (LIA). The isotopic signature shows that the percentage of oxygen sourced from photosynthesis was greater during the LIA. This may indicate a greater rate of photosynthesis than at present. However, we know that when sea ice covers the ocean surface, it prevents the influx of atmospheric oxygen, while sunlight penetration through the ice keeps a high rate of photosynthesis and production of biological oxygen. Therefore, it is also possible that during the LIA, sea‐ice cover was much more extensive than today. Key Points: Oxygen isotopic evidence for a recent dramatic shift in the North Atlantic source region of deep water‐masses The isotopic measurements suggest high extent of ice cover and/or higher primary production rates during the Little Ice Age These new observations can serve as a benchmark for climate models